From Culture to Concept: Deep Learning Approaches to Science Literacy through Baduy Local Knowledge in Banten High Schools - Nulhakim, Lukman (International Journal of Education and Learning Studies, 2025)
This study explores the integration of Baduy Indigenous knowledge into high school science learning in Banten, Indonesia, using a deep learning approach. Grounded in qualitative case study methodology, data were collected through classroom observations, student reflections, interviews, and teaching materials. The findings reveal that contextualizing scientific concepts through Baduy ecological wisdom—such as chemical-free farming and forest conservation—enhanced students’ conceptual understanding, engagement, and cultural identity. Students demonstrated deep learning indicators, including critical thinking, systems thinking, and knowledge transfer, especially when engaging with science through culturally embedded narratives. The presence of a Baduy community member in the classroom further validated cultural interpretations and strengthened socially mediated learning. This research shows that Indigenous knowledge, when used as a pedagogical core rather than supplementary content, can foster meaningful, ethical, and place-based science education. It highlights the importance of culturally responsive pedagogy in promoting scientific literacy and identity affirmation in underrepresented communities.